Solution of Population Growth Rate Linear Differential Model via Two Parametric SEE Transformation - Ali Moazzam; Hira Aslam; Naila Tabassum; Emad A. Kuffi (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2023)
The integral transformations is a complicated function from a function space into a simple function in transformed space. Where the function being characterized easily and manipulated through integration in transformed function space. The two parametric form of SEE transformation and its basic characteristics have been demonstrated in this study. The transformed function of a few fundamental functions along with its time derivative rule is shown. It has been demonstrated how two parametric SEE transformations can be used to solve linear differential equations. This research provides a solution to population growth rate equation. One can contrast these outcomes with different Laplace type transformations